Genetic Variations and Clinical Features of NPHS1-Related Nephrotic Syndrome in Chinese Children: A Multicenter, Retrospective Study - Rong, Liping; Chen, Lizhi; Rao, Jia; Shen, Qian; Li, Guomin; Liu, Jialu; Mao, Jianhua; Feng, Chunyue; Wang, Xiaowen; Wang, Si; Kuang, Xinyu; Huang, Wenyan; et al. (Frontiers in Medicine, 2021)
Introduction: Few studies have addressed the genetic spectrum of NPHS1 variants in Chinese children with nephrotic syndrome. In this multicenter study, the clinical manifestations and features of NPHS1 variants in Chinese children with nephrotic syndrome were researched. Method: Genotypical and phenotypical data from 30 children affected by NPHS1 variants were collected from a multicenter registration system in China and analyzed retrospectively. Results: The patients were divided into two groups: congenital nephrotic syndrome (CNS [n = 24]) and non-CNS (early onset nephrotic syndrome [n = 6]). Renal biopsy was performed on four patients in the non-CNS group, revealing minimal change disease in three and focal segmental glomerulosclerosis in one. A total of 61 NPHS1 variants were detected, involving 25 novel variants. The “recurrent variants” included c.928G>A(p.Asp310Asn) in eight patients with CNS, followed by c.616C>A(p.Pro206Thr) in four, and c.2207T>C (p.Val736Ala) in three. Steroid treatment was applied in 29.2% (7/24)of the patients in the CNS group and 50% (3/6) of the patients in the non-CNS group. One patient in each group experienced complete remission but relapsed subsequently. Immunosuppressants were administered to three patients in the non-CNS group, eliciting an effective response. In the CNS group, three patients underwent renal transplantation and six died mainly from infection. Conclusion: Variants of NPHS1 cause CNS and early childhood-onset nephrotic syndrome. NPHS1 variants in Chinese individuals with nephrotic syndrome (NS) were mainly compound heterozygous variants, and c.928G>A(p.Asp310Asn) in exon 8 may act as a recurrent variant in the Chinese population, followed by c.616C>A(p.Pro206Thr) in exon 6. Steroids and immunosuppressants may be effective in selected patients.